Failure analysis of gearbox in CRH high-speed train. (November 2019) - Hu, Yongxu; Lin, Jianhui; Tan, Andy Chit
Abstract: In this study, an analysis was conducted to investigate how misaligned cardan shaft could result in failure of gearbox in CRH high speed train. The cardan shaft was used to provide rotating motion from motor to gearbox. The study began with an analysis of the failure of a serviced gearbox in CRH train. It was revealed that rotation of misaligned cardan shaft was the most likely candidate for gearbox fracture which led to total failure of the train. To explain how misaligned cardan shaft led to failure, a kinetic analysis of misaligned cardan shaft was first performed by analytically calculating the force acted on gearbox and followed by an experimental test to validate the results. The results from kinematic analysis indicated a small offset of cardan shaft led to huge inertial force and frictional force acting on the universal joints. These forces resulted in bending load acting on bevel gear shaft and led to vibration. The vibration caused excessive rubbing of the connection and resulted in looseness of the fit. Eventually the gearbox was fractured by violent collision. An experiment was conducted to validate the failure process. The experimental results confirmed the rotational misaligned cardan shaft caused impact between shaft and bearing block. Consequently, this paper proposes a detection method to monitor cardan shaft used in CHR high speed train. For the first time this work conforms it was essential to consider transport acceleration when analyzing unbalance force due to misalignment of cardan shaft. Highlights: Systematic studies of kinetics and dynamics of misaligned cardan shaft in rotation. Design of experimental cardan shaft and test set-up to mimic real life operation. Investigation on looseness of interference fit of flange leading to gearbox failure. Confirming the inertial force caused by transport acceleration is the main reason leading to looseness. Study on influence of misalignment on the friction force of cardan shaft.